The Effect of Auditor Switching and Auditor Independence on Audit Quality With Audit Fees As A Moderating Variable - Fellicia Fellicia; Christina Dwi Astuti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Audit quality is a crucial element in ensuring the reliability of financial reporting, particularly for property and real estate companies that operate with complex business structures and high levels of risk. This study aims to examine the effect of auditor switching and auditor independence on audit quality, with audit fee as a moderating variable, as well as firm age and firm size as control variables. A quantitative approach was employed using panel data from 64 property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, with a total of 167 firm-year observations. The data were analyzed using panel data regression with the Fixed Effect Model, processed through EViews software. The results show that auditor switching has a positive effect on audit quality, while auditor independence, as measured by audit tenure, does not show a significant impact. Furthermore, audit fee does not significantly moderate the relationship between auditor switching and auditor independence on audit quality. This study contributes theoretically by enriching the understanding of the role of structural and compensation factors in maintaining audit quality and offers practical implications for managers and regulators in designing more effective audit policies. Future research is recommended to use more diverse indicators of audit quality and include other industrial sectors to enhance the generalizability of the findings.